Evaluation of Sox2 binding affinities for distinct DNA patterns using steered molecular dynamics simulation. Issue 11 (9th October 2017) - Yesudhas, Dhanusha; Anwar, Muhammad Ayaz; Panneerselvam, Suresh; Kim, Han‐Kyul; Choi, Sangdun
Abstract : Transcription factors (TFs) are gene expression regulators that bind to DNA in a sequence‐specific manner and determine the functional characteristics of the gene. It is worthwhile to study the unique characteristics of such specific TF‐binding pattern in DNA. Sox2 recognizes a 6‐ to 7‐base pair consensus DNA sequence; the central four bases of the binding site are highly conserved, whereas the two to three flanking bases are variable. Here, we attempted to analyze the binding affinity and specificity of the Sox2 protein for distinct DNA sequence patterns via steered molecular dynamics, in which a pulling force is employed to dissociate Sox2 from Sox2–DNA during simulation to study the behavior of a complex under nonequilibrium conditions. The simulation results revealed that the first two stacking bases of the binding pattern have an exclusive impact on the binding affinity, with the corresponding mutant complexes showing greater binding and longer dissociation time than the experimental complexes do. In contrast, mutation of the conserved bases tends to reduce the affinity, and mutation of the complete conserved region disrupts the binding. It might pave the way to identify the most likely binding pattern recognized by Sox2 based on the affinity of each configuration. The α2‐helix of Sox2 was found to be the key player in the Sox2–DNA association. The characterization of Sox2's binding patterns for the target genes in the genome helps in understanding of its regulatory functions. Abstract : Transcription factor Sox2 recognizes a 6‐ to 7‐base pair consensus DNA sequence (CTTTGTT); the central four bases of the binding site are highly conserved, whereas the two to three flanking bases are variable. This study emphasizes on the binding affinity and specificity of Sox2 with distinct DNA sequence patterns using extensive computational protocols (steered molecular dynamics and umbrella sampling). The results revealed that the first two stacking bases of the binding site have an exclusive impact on the binding affinity and the mutation of the conserved bases drastically reduces the binding affinity of Sox2.